Adaptive management; adaptive co-management; adaptive governance: what's the difference?. Issue 1 (2nd January 2017) - Hasselman, Lyndal
ABSTRACT: Since the late 1970s, the literature on adaptive management has grown markedly. Active and passive forms have been identified, implementation trialled and institutional requirements explored. Adaptive management is now an accepted quality of governance and, in some cases, a legislative requirement of natural resource management. The concept is widely encouraged; yet, there remain high rates of implementation failure. Confusion on the definition of adaptive management is one cause of implementation errors, with researchers, natural resource managers and policy-makers talking and acting cross-purposes. Adaptive management is variously described as 'experimental management', 'learning by doing' and 'structured decision-making'. Adding to the confusion, the related terms adaptive co-management and adaptive governance have also emerged. This article analyses the definitions of adaptive management, adaptive co-management and adaptive governance, highlighting confusion within definitions, between definitions and misinterpretations of definitions. Furthermore, interchangeable use of these terms suggests a lack of additionality. Differing epistemologies, and consequently, interpretations of uncertainty, are shown to be at the core of misinterpretations and ensuing confusion. The findings identify distinguishing dimensions of adaptive management, adaptive co-management and adaptive governance before proposing clear definitions.